Genetic parameters for morphometric traits of africanized honeybee drones - Rodrigues, Marisa Clemente (2016)
Available information on Africanized honeybee breeding, especially regarding the male component of the species, is almost non-existent. The aim of this study was to estimate genetic correlations for weight and morphometric traits of drones at emergence and maturity, so that in future breeding programs these traits can act as selection criteria through their genetic value. Phenotypic and genetic parameters were estimated for weight and morphometric traits such as weight (W), total length (TL), abdomen length (AL), abdomen width (AW), wing length (WL) and wing width (WW) at drones’ emergence (E) and maturity (M). Single-trait and two-trait models were used and parameters such as genetic variance, heritability and genetic correlations were calculated using a Bayesian approach. Results: A total of 1117 drones were measured at emergence and 336 again at maturity. In single-trait models, heritabilities were 0.78, 0.52, 0.56, 0.93 and 0.92 for WE, WM, ALM, WL M and WWM, respectively. The genetic correlation between WE and the remaining traits ranged from 0.55 to 0.83. Conclusions: Traits such as W E, WM, TLM, ALM, WLM, WWM, when considered individually, can be used as selection criteria because genetic variance for these traits accounted for more than 50% of the total phenotypic variance. The WE combined with other traits assessed at drones' emergence can be used in breeding programs for the improvement of the aforementioned traits. Breeding selection for weight or total length at emergence promises considerable genetic progress for weight at maturity. The combination of genetic parameters for reproductive and morphometric traits in drones properly supported by breeding programs relying on artificial insemination, for an effective mating control, will likely help in clarifying this possibility.